2022
DOI: 10.1111/pde.14938
|View full text |Cite
|
Sign up to set email alerts
|

Hydroa vacciniforme‐like lymphoproliferative disorder: A retrospective study on clinicopathological characteristics of 32 cases

Abstract: Hydroa vacciniforme-like lymphoproliferative disorder (HVLPD) is an Epstein-Barr virus (EBV)-associated cutaneous T/NK cell lymphoproliferative disease that mainly affects children and adolescents. 1 Classic hydroa vacciniforme (HV) is characterized by papulovesicular eruptions that evolve into crusts and heal with pitted scars in sunexposed areas. Systemic symptoms, including fever, lymphadenopathy, and hepatosplenomegaly, are absent. Atypical or severe HV has mainly been reported in East Asia and Latin Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…Another retrospective study of 32 patients between 1.5–21 years of age found that at presentation, 6 patients only had skin lesions, whereas 26 patients showed both skin lesions and systemic symptoms, including fever, lymphadenopathy, and hepatosplenomegaly. As the disease progressed, systemic symptoms occurred in all patients, and after a median follow-up time of 6 months, 15 patients had died [6 ▪ ]. Finally, a study of nine patients found that eight patients who received combinations of thalidomide, interferon, prednisone, acyclovir, and/or isotretinoin improved, whereas one patient who received chemotherapy died, corroborating reports noting that traditional chemotherapy may be associated with poor outcome [7].…”
Section: Idiopathic Photodermatosessupporting
confidence: 72%
“…Another retrospective study of 32 patients between 1.5–21 years of age found that at presentation, 6 patients only had skin lesions, whereas 26 patients showed both skin lesions and systemic symptoms, including fever, lymphadenopathy, and hepatosplenomegaly. As the disease progressed, systemic symptoms occurred in all patients, and after a median follow-up time of 6 months, 15 patients had died [6 ▪ ]. Finally, a study of nine patients found that eight patients who received combinations of thalidomide, interferon, prednisone, acyclovir, and/or isotretinoin improved, whereas one patient who received chemotherapy died, corroborating reports noting that traditional chemotherapy may be associated with poor outcome [7].…”
Section: Idiopathic Photodermatosessupporting
confidence: 72%
“…Through the report of a series of patients, some groups have provided new information that has allowed us to recognize a broader spectrum of the disease, both clinically and with some variability in the histopathological features as well. [4][5][6][7][8] Here, we present an original case of an HV LPD with an atypical clinical presentation and a fatal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Through the report of a series of patients, some groups have provided new information that has allowed us to recognize a broader spectrum of the disease, both clinically and with some variability in the histopathological features as well. 4–8…”
Section: Introductionmentioning
confidence: 99%